Centrifuge Testing and Seismic Response Analysis for Uplift Behavior of Spread Foundation Structures on Rock - Suzuki, Takuya; Ogase, Yuki; Honda, Tsuyoshi; Akita, Shodo; Yabushita, Naoto; Nakamura, Naohiro (Frontiers in Built Environment, 2016)
The uplift behavior of structures subjected to severe seismic motion has not been clarified. This paper presents experimental and analytical studies conducted for clarifying this problem of spread foundation structures on rock. First, centrifugal loading tests are conducted to determine the uplift behavior of these structures, and the uplift behavior of these structures is confirmed. Then, simulation analyses are performed using a three-dimensional FE model and the accuracy of these analyses is confirmed. A comparison between test and analyses results clarified the important analytical conditions required for maintaining analysis precision and the limit of analysis precision.